Are cutout handles used when available in real occupational settings? Description of grips and upper extremities movements during industrial box handling - Silva, Luciana C. C. B.; Oliveira, Ana B.; Alem, Michele E. R.; Paschoarelli, Luis Carlos [UNESP]; Coury, Helenice J. C. G. (IOS Press, 2012)
In order to achieve better postures and decrease musculoskeletal risks adequate design of hand/box couplings for manual materials handling (MMH) are still needed. No studies evaluating upper limb movement thorough direct measurements during box handling in workplace were identified in the literature. In this study we describe the types of grip and movements adopted by ten workers when handling redesigned boxes with cutout handles between different heights on industrial pallets. The new handles were used by 90% of the workers through different types of grip. Electrogoniometric measurements showed relatively safe forearm and wrist movements, although elbow inadequate range of movement was recorded. Despite the good acceptance of the cutout by workers, the new design requires extra internal space in the boxes reducing applications for this alternative of box.
Keywords: industrial handling; movement recording; electrogoniometer; work related musculoskeletal disorders; wrist